Heat stress and physiological changes among workers at steel manufacturing industry in Shah Alam, Selangor / Syakimatun Aliah Mohd Daud ... [et al.] - Mohd Daud, Syakimatun Aliah; Ishak, Ahmad Razali; Azalan, Nurul Imanina; Ismail, Rodziah; Mohd Tahir, Mohd Pozi (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Heat stress is recognized as a severe physical hazard which can cause health related problems at workplace. Theoretically, the effect of heat stress tends to cause physiological changes such as raising body temperature and also increase both heart rate and blood pressure. The purpose of this study was to determine the heat stress level among workers at a steel manufacturing industry in Shah Alam. A total of 71 workers from six workstations were included in this study. The level of heat stress was identified using Heat Strain Score Index (HSSI) questionnaire while the ambient temperature at various workstations was measured using Wet Bulb Globe Temperature (WBGT). Based on the HSSI, 60, 30 and 10% of workers in the steel manufacturing industry were working in the red, yellow and green zones respectively. However, no correlation was observed between ambient temperature and physiological response among them. Although these findings showed no extreme environmental heat stress experienced by the workers, mitigation measures should be taken to control future heat exposure.